Clinical Utility of Plasma uPA and PAI-1 as a Prognostic Biomarker in Breast Cancer - Singh, MD, Dr. Subhash; Singh, MD, Dr. Smita; Kumar, DNB, Dr. Rakesh; Sharma, MD, Dr. Sunita; Singh, MD, Dr. Nain (International Journal of Innovative Research in Medical Science, 2025)
Background: Breast cancer represents the most frequently diagnosed form of cancer on a global scale and stands as the primary cause of cancer-related mortality among women. Metastasis of tumors constitutes a significant factor contributing to mortality in breast cancer cases. The urokinase-type plasminogen activator system, including uPA, uPAR, PAI-1 and PAI-2, is crucial for tumor progression and metastasis. Their combination is a validated prognostic marker for both node-negative and node-positive breast cancer, guiding treatment decisions for early breast cancer. This study aims to analyse uPA and PAI-1 levels in breast carcinoma patients and their correlation with disease stage, hormonal status, and potential use as prognostic indicators. Objective: To estimate the plasma levels of uPA and PAI-1 in patients with breast carcinoma and compare them to those in the control group. To correlate these markers (uPA and PAI-1) with other clinicopathological parameters. Methods: A cross-sectional analytical study was conducted on 30 biopsy-proven breast cancer patients. Blood samples were collected to analyse uPA and PAI-1 levels and coagulation profiles. The correlation between uPA and PAI-1 levels and other clinicopathological parameters was studied. Results: Our study observed a statistically significant association of uPA levels with increasing tumor size, higher tumor stage, lymphadenopathy and higher ki67 index (<0.05). On the contrary, the association of uPA levels with ER/PR and HER2/neu receptor status was insignificant. The association of high PAI-1 levels with higher clinical stage and ER-negative status of the tumor was statistically significant. (p<0.05). Both uPA and PAI-1 show co-elevation in most breast cancer patients. Conclusion: Plasma uPA/PAI-1 levels may provide important information in the risk stratification of patients with breast cancer and act as potential prognostic biomarkers.